2020
DOI: 10.15659/ankad.v4i3.107
|View full text |Cite
|
Sign up to set email alerts
|

Coğrafya Öğretmenlerinin Teknolojik Pedagojik Alan Bilgisi (TPAB) Yeterliklerini Ölçmeye Yönelik Hazırlanan Bir Başarı Testinin Geliştirilmesi

Abstract: Başarı testi geliştirme, coğrafya eğitimi, teknolojik pedagojik alan bilgisi KeywordsAchievement test developing, geography education, technological pedagogical content knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Sanat, K., Nurbol, U., Bakhadurkhan, A., Anargul, S., Zukhra, D., & Gulfa, K. (2022) In terms of the content of the geography course, it is quite suitable for benefiting from and using technology in terms of purpose and achievement. It has been found that the use of technology in the geography lesson will help permanent learning and increase attention and motivation (Aktekin & Çoban, 2012;Çiftçi & Dikmenli, 2018;Dikmenli & Ünaldı, 2013;Dündar & Ünaldi, 2020;Kesler, 2007;Russell, 2007). For this reason, it is important to determine which technologies are used in geography lessons; how often these technologies are used; and if there are problems experienced in this process, what are they.…”
Section: Technological Pedagogical Knowledge (Tpk)mentioning
confidence: 99%
“…Sanat, K., Nurbol, U., Bakhadurkhan, A., Anargul, S., Zukhra, D., & Gulfa, K. (2022) In terms of the content of the geography course, it is quite suitable for benefiting from and using technology in terms of purpose and achievement. It has been found that the use of technology in the geography lesson will help permanent learning and increase attention and motivation (Aktekin & Çoban, 2012;Çiftçi & Dikmenli, 2018;Dikmenli & Ünaldı, 2013;Dündar & Ünaldi, 2020;Kesler, 2007;Russell, 2007). For this reason, it is important to determine which technologies are used in geography lessons; how often these technologies are used; and if there are problems experienced in this process, what are they.…”
Section: Technological Pedagogical Knowledge (Tpk)mentioning
confidence: 99%